Fenton Oxidation Of Amine Waste - YOUSEF, NIK FAHIMEH (Universiti Teknologi Petronas, 2005)
Amine carry over is a commonly-discussed problem in gas plant utilizing amine as a medium to obliterate acid gases from the incoming gas stream. Amine carry over will potentially end up in the effluent water thus, if improperly discharge will pollute the environment. Mixture of water with high amine concentration will resort to high chemical oxygen demand value, which is a direct and almost accurate measure of contaminants in water . The higher the COD value, the higher the concentration of contaminants in water. Mixture of amine with water is a tenacious and well mixed mixture, hence, to separate themis a challenge. Thisprojectis doneto study the COD value reduction of amine waste using Fenton reagent. The parameters that are studied are the effect of Ferum as the catalyst and also the optimum Fe : H202 which will give a higher COD value reduction.